Coccophagus scutellaris (Hymenoptera: Aphelinidae): A Highly Effective Biological Control Agent of Soft Scale Insects (Hemiptera: Coccidae) in Egypt - Shaaban Abd-Rabou (Psyche: A Journal of Entomology)
About 953000 individuals of the cosmopolitan parasitoid, Coccophagus scutellaris (Dalman) (Hymenoptera: Aphelinidae), were released and evaluated during 2009-2010 for the control of the following soft scale insects (Hemiptera: Coccidae) infesting the following economic crops in Egypt: Ceroplastes rusci on citrus in Beni Seuf, Ceroplastes floridensis Comstock on citrus in Gharbiya, Coccus hesperidum L. on guava in Giza, Pulvinaria floccifera (Westwood) on mango in Sharqiya, Pulvinaria psidii Maskell on mango in Ismailia, Saissetia coffeae (Walker) on olive in Marsa Matruh, and Saissetia oleae (Oliver) on olive in the Northern Coast. The population of C. scutellaris showed a significant correlation with the build up of the population of the soft scale insects population in all of the release sites studied. The maximum rate of parasitism of the other species of parasitoids associated with soft scale insects at the release sites decreased after the release of C. scutellaris.